Показники точності визначення координат джерел радіовипромінювання у пеленгаторній мережі HF діапазону - Кобзєв, Анатолій Васильович; Мурзін, Михайло Вячеславович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Проводиться оцінка граничних можливостей по точності визначення координат джерел радіовипромінювання у пеленгаторній мережі HF діапазону при розміщенні її на території України. Виводяться розрахункові співвідношення для обчислення робочих зон визначення координат джерел радіовипромінювання і обговорюються результати розрахунків при мінімально можливому числі пеленгаторів мережі (3, 4), що забезпечують круговий контроль простору. Результати розрахунків робочих зон відображають граничні можливості по точності визначення координат, оскільки характеристики мережі (просторовий рознос пеленгаторів і реальна точність пеленгації) обрані гранично можливими.

Direction finding networks have found application in radio monitoring, radio intelligence and passive radar systems. The operation of the direction-finding network in the short-wave range has a number of distinctive features, namely, long range of direction finders (up to several thousand km) due to ionospheric propagation of radio waves and high sensitivity of narrow-band signal receivers. In addition, the distance between direction finders can be hundreds or thousands of kilometers. Therefore the calculations should be carried out due to the location of the direction finders and radio sources on a spherical surface. In this work, analytical relationships are obtained for calculating the accuracy indicators of the estimation of coordinate information (latitude and longitude) at the output of the direction finding network in a rather general form in relation to the features of the short-wave range. The problem is solved in a geographic coordinate system for an arbitrary number of direction finders (two at least) and with their arbitrary location on the surface of Earth. To carry out a comparative analysis and assess the quality of coordinate information for various options for placing direction finders, it is proposed to display accuracy indicators using working zones (for example, round). The use of working areas allows a visual assessment on the map overall spatial pattern for accuracy indicators direction-finding network. The results of the calculation of working areas direction-finding network shortwave when placing it on the territory of Ukraine in the case of the smallest real errors direction-finding, and a mutual separation distance finders maximum permissible selected. The calculation results reflect the limiting possibilities for the accuracy of determining the coordinates of radio emission sources for such a direction finding network with a minimum number of direction finders (3 or 4). The given method of calculating working zones allows for the implementation of the best accuracy indicators to choose a specific option for placing direction finders on the territory of the country, taking into account the influence of all factors (approach of positions, availability of access roads, conditions for accommodating service personnel, etc.). As an example, the work considers 3 options for the location of direction finders with the maximum separation on the territory of Ukraine. The developed technique can also be used for other passive radar systems with direction finding coordinates, when it is necessary to take into account the spherical form of the Earth. Such a system can include two or more aerial reconnaissance aircraft with direction finders on board, as well as one aircraft or unmanned vehicle that determines coordinates by the method of multiple direction finding on the flight route.
Indicators of accuracy for determining the coordinates of radio emission sources in the short wave direction finding network
Keywords: граничні можливості по точності; контроль радіовипромінювань; boundary possible accuracy; radio emission control